A novel catalyst CuO-ZrO2 doped on Cl− activated bio-char for Hg0 removal in a broad temperature range. (15th April 2018) - Tang, Le; Li, Caiting; Zhao, Lingkui; Gao, Lei; Du, Xueyu; Zeng, Jiawen; Zhang, Jie; Zeng, Guangming
Graphical abstract: Highlights: The catalyst used Cl − activated bio-char as the support. CuO-ZrO2 interaction resulted in superior activity for Hg 0 removal. The catalyst possessed well SO2 and H2 O resistance and stable Hg 0 removal activity. Hg 0 adsorption mainly existed at low temperature while oxidation was opposite. Abstract: To obtain a new low-cost catalyst that possesses well Hg 0 removal activity in a broad temperature range, a series of Cu-Zrx /Cl-BC catalysts were synthesized with the application of bio-char which was activated by NH4 Cl. CuO-ZrO2 as the active component largely improved Hg 0 removal activity of the catalysts. The catalysts were characterized by SEM-EDX, BET, XRD, H2 -TPR, XPS and FT-IR. When the CuO-ZrO2 loading value was 10%, Cu-Zr10 /Cl-BC reached the best Hg 0 removal efficiency (98.87%) at 120 °C and maintained over 80% until 240 °C. O2 was of benefit to Hg 0 removal process especially at high temperature because it could regenerate the lattice oxygen which participated in the removal reaction. In addition, Hg 0 removal was mainly determined by adsorption at low temperature and the function of oxidation increased at high temperature. The characterization results indicated that the superior performance of Cu-Zr10 /Cl-BC might be ascribed to lower crystallinity, stronger redox ability and better texture properties which resulted from the interaction of CuO and ZrO2 . The mechanism for Hg 0 removal over Cu-Zr10 /Cl-BC was also proposed on the basis of above studies.